The use of continuous thoracic paravertebral nerve block under direct vision for postoperative pain management in thoracic surgery - Tanyong Pipanmekaporn (2018)
Objective: The purpose of the present study was to determine the quality of analgesia of continuous thoracic paravertebral nerve block after thoracic surgery by inserting a catheter under direct vision and assessing complications related to the analgesia technique. Material and Method: Thirty patients with ASA I-III scheduled for pulmonary resection were enrolled in the present prospective study. Posterolateral thoracotomy was done by one surgeon. At the end of the operation before chest closure, a 16 G Touhy needle was inserted under direct vision at distance 5 cm from midline below incision interspace. The needle was advanced slowly until its tip bulged into the potential space, which is called paravertebral space, beneath the parietal pleura. Then, passing a catheter until the distal tip laid two to three intercostal spaces above the incision. A bolus of 15 to 20 ml of 0.5% levobupivacaine was given via a catheter and a continuous infusion with 0.25% levobupivacaine at rate 0.1 ml/kg/hr. Rescue treatment consisted of intravenous morphine and oral analgesic drugs. Numeric rating scale (NRS at rest, movement and cough), an amount of morphine consumption and complications related to analgesia were assessed at 2, 6, 12, 24, 48, 72, and 96 hours after operation. Results: All patients completed the present study. The median numeric rating scale at rest in 24, 48, 72 and 96 hours after the operation was 2 (0-3), 0.5 (0-2),0 (0-2) and 0 (0-1) whereas the median numeric rating scale at deep breathing and coughing was 3.5 (2-5), 2 (2-4), 2 (1-3) and 2 (0-2). The median cumulative morphine consumption in 48 and 72 hours was 2 (0-4) and 3 (0-6) mg. Ten patients did not require additional morphine during the postoperative period. One patient experienced hypotension after a bolus of levobupivacaine for a few hours and recovered after supportive treatment. Conclusion: The use of continuous thoracic paravertebral blockade under direct vision technique offered satisfactory pain control and less complications. It could be considered as an alternative when thoracic epidural block is difficult to access.